Processo eletrônico de pedido de patente no Núcleo de Inovação Tecnológica do Instituto Federal de Roraima - Silva, Cleber Medeiros (2020)
In view of the need to optimize intellectual property management processes, within the scope of Science and Technology Institutions, the objective of this study was to develop a prototype for the electronic patent application process at the Federal Institute of Roraima and to propose strategies for its implantation. This research is characterized as applied, cross-sectional, exploratory and descriptive, using qualitative and quantitative methods. The study sample consisted of technical staff and professors involved in the IFRR research and innovation areas. Data collection and analysis were made based on the Design Thinking approach, which incorporates interviews, benchmarks, observations and meetings. The results show that the internal patent application process at IFRR is still in the maturation phase and that the prototype developed for the electronic process, together with the user manual, can contribute to the improvement of the process.